A series-resonant inverter with extended topology and pulse-density-modulation control for induction heating applications - Pavlo Herasymenko; Volodymyr Pavlovskyi; Oleg Yurchenko (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This paper presents a series-resonant inverter (SRI) with an extended topology using a pulse-density modulation (PDM) control method. Theoretical analysis shows that the use of the SRI with extended topology and the PDM control (extended PDM-SRI) allows reducing the fluctuation of the SRI output current by more than 40% at the quality factor of 5 compared to a conventional SRI with the traditional PDM control. To eliminate drawbacks of the extended PDM-SRI, specificities of PDM switching sequences to ensure the zero-voltage-switching (ZVS) operation are discussed in detail, and a solution to the voltage imbalance across the capacitors of the extended topology is proposed. Simulation analysis of the extended PDM-SRI confirmed the effectiveness of using the proposed solutions to eliminate the drawbacks. The feasibility of the proposed SRI is confirmed by testing on a 2.2 kW experimental setup.